(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2024)
A group divisible (GD) design is said to be Singular (S) if ; Semi regular (SR) if and rk – v = 0; Regular (R) if and . In the paper, a new procedure of constructing SRGD design with and , is proposed from a parent SRGD after reducing number of treatment and same number of blocks without disturbing its Semi-Regularity property. It privileges the experimenters to decrease the number of treatment without affecting the number of blocks. Such designs are useful in civil engineers, Agricultural experiments and others. AMS Subject Classification: 05 B05